A novel peptide oyster-derived antimicrobial peptide against clinical carbapenem-resistant Acinetobacter baumannii - Rui Hou; Yihua Cai; Shida Xu; Dandan Ma; Ning Su; Shanshan Wang; Hongmei Mo; Mian Peng (Frontiers in Marine Science, 2026)
Background The escalating prevalence of multidrug-resistant pathogens, specifically carbapenem-resistant Acinetobacter baumannii (CR-AB), underscores the urgent need for novel antimicrobial strategies. Antimicrobial peptides (AMPs) offer a viable alternative to conventional antibiotics. Methods We discovered a novel AMP, designated OAMP, from oyster hemolymph and evaluated its antimicrobial efficacy against a spectrum of pathogens, including five clinical CR-AB strains. The synergistic potential of OAMP with meropenem, tigecycline, and colistin was assessed via checkerboard assays. Safety profiles were determined through cytotoxicity and hemolysis assays. Results OAMP exhibited potent broad-spectrum activity, effectively inhibiting CR-AB strains with MIC values of 4–8 µM. In combination therapies, OAMP demonstrated additive to synergistic effects with conventional antibiotics, facilitating a reduction in antibiotic dosage. However, safety assessments revealed cytotoxicity and hemolytic activity at MIC levels, indicating a narrow therapeutic window. Conclusions OAMP shows significant promise as a potent antibacterial agent and an effective adjuvant for combinatorial therapy against CR-AB. Future studies should focus on structural optimization to mitigate toxicity and enhance stability for clinical application.

Characteristics and primary controls of coral reef carbonate karstification in the South China Sea since the Miocene - Yang Yang; Kefu Yu; Bin Xiong; Wei Jiang; Shendong Xu; Rui Wang; Tianlai Fan (Frontiers in Marine Science, 2025)
Coral reef karstification plays a vital role in sea-air CO 2 exchange, yet its mechanisms remain unclear. This study employs an 878.22-m coral reef sequence (dating to19.6 Ma) from Well CK2 in the Xisha Islands, South China Sea (SCS), to investigate karstification processes, including their signatures, primary controls, and implications for marine carbonate dissolution in global carbon cycling. Petrological and geochemical analyses of CK2 revel distinct karstification characteristics, including: (1) higher surface porosity 25–30%), with randomly distributed pores and fractures of variable sizes and shapes; (2) yellowish-brown to black impregnations; (3) micritic cements accompanied by well-crystallized mineral crystals, and (4) moderately well-sorted and rounded grains. Geochemical signatures show elevated 8787 Sr/ 86 Sr, Mn content, and Mn/Sr ratios, coupled with depleted δ¹³C, δ 18 O and Sr content. These features collectively indicate that karstification in CK2 was dominated by non-selective dissolution and recrystallization processes, principally occurring at the mixing zone in meteoric water systems during prolonged subaerial exposure. Karstification signatures varied across geological epochs, implying different controlling mechanisms. Late Miocene (12.6–10.2 Ma), driven by sustained sea-level fall, exhibited an extreme 87 Sr/ 86 Sr shift and severe erosion. Pleistocene (2.2–1.8, 1.1–0.89, 0.29 and 0.2 Ma), influenced by frequent sea-level fluctuations and warm, humid environments linked to glacial-interglacial cycle and Asian monsoon, displayed the highest surface porosity (15–40%, mean 25%), ochre to tawny impregnations, and micritized cements, along with negative δ¹³C-δ 18 O and elevated 87 Sr/ 86 Sr and Mn/Sr ratios. In contrast, the Middle Miocene Climatic Optimum (16.6–16 Ma) lacked typical karst characteristics but comprised of well-rounded and sorted coral gravels, suggesting reef-building organisms mediate karstification via substrate architecture. These findings demonstrate that sea-level changes and climate conditions control coral reef karstification intensity. Concurrently, dissolution during karstification may significantly modify ocean alkalinity and dissolved inorganic carbon, with potential feedback on carbon cycling in future climate scenarios.

Millennial-scale surface hydrological variability in the tropical eastern Indian Ocean linked to Northern Hemisphere high latitudes - Rui Cui; Peng Zhang; Jian Xu; Ann Holbourn; Wolfgang Kuhnt (Frontiers in Marine Science, 2025)
Surface hydrology in the tropical eastern Indian Ocean significantly impacts low-latitude climate processes including the Indonesian-Australian Monsoon and the Indian Ocean Dipole. Deciphering the evolution of surface hydrology and driving mechanisms is thus important to better understand low-latitude and global climate change. Here, we present ~206 yr-resolved temperature and salinity records of surface waters spanning the past ~31 kyr, based on δ 18 O and Mg/Ca ratio of Globigerinoides ruber from Core SO18567 retrieved offshore northwestern Australia in the tropical eastern Indian Ocean. By integrating new records with published paleo-oceanographic and -climatological records, we found that increasing sea surface temperature and decreasing salinity in the tropical eastern Indian Ocean during the Heinrich stadial 1 and the Younger Dryas could be attributed to collapse of the Atlantic Meridional Overturning Circulation (AMOC). Melting of Northern Hemisphere ice sheets would have led to a southward shift of the Intertropical Convergence Zone (ITCZ) and reduced transport of warm surface waters from the low latitudes to the Northern Hemisphere high latitudes. In addition, our results indicate that the onset of the last deglacial warming in low latitudes was linked to weakening of the Hadley circulation and AMOC due to warming of Northern Hemisphere high latitudes, rather than raised global atmospheric CO 2 concentration.

Digital twin-driven safety management and decision support approach for port operations and logistics - Kan Wang; Hang Xu; Hao Wang; Rui Qiu; Qianqian Hu; Xiaolei Liu (Frontiers in Marine Science, 2024)
Ports are of great significance in processing cargo containers and facilitating global marine logistics. Nevertheless, the susceptibility of the container shipping network for hazardous cargo is likely to intensify in the event of a significant disruption at a major port, such as adverse weather conditions, inadequate management practices, or unforeseen catastrophes. Such situations require the deployment of port protection emergency response and prevention in advance. This study proposes a digital twin (DT) model that employs extensive and trajectory data within containers to comprehensively analyze the occurrence of hazardous cargo failures within the port storage process. The virtual models of physical entities in the port are created through a data-driven approach, and the behavior of these entities in a port environment with big data is then simulated. A combination of a convolutional neural network (CNN) and a long short-term memory (LSTM) algorithm is employed to provide predictions for the service layer of the DT system. The predicted correlation coefficients of temperature and humidity in the container reach 0.9855 and 0.9181, respectively. The developed system driven by DT models integrated with a CNN and the LSTM algorithm can more effectively assist the safety manager in achieving prevention in port operations. This study enables marine authorities and decision-makers to optimize emergency procedures, thereby reducing the probability of accidents in port operations and logistics.

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

The identification of toll-like receptor genes in large yellow croaker (Larimichthys crocea): provides insights into its environmental adaptation to biological and abiotic stresses - Ting-Yan Yao; Qing-Tao Miao; Xuan-Yang Sun; Chen Rui; Qing-Ping Xie; Xu-Bo Wang (Frontiers in Marine Science, 2024)
Large yellow croaker ( Larimichthys crocea ), the most developing fish of China, suffering from both biotic and abiotic stressors. A genome-wide study was performed for the first time to investigate the roles of Toll-like receptor genes in large yellow croaker ( LcTLRs ) working in hypoxia response and Aeromonas hydrophila infection. 12 TLR genes were identified and annotated, and phylogenetic tree, analysis of structure and motifs demonstrated that TLRs were highly conserved. To further investigate the LcTLRs under environmental stress, expression pattern analysis of hypoxic response and Aeromonas hydrophila infection revealed that there were nine and six members of LcTLRs showing significant differential expression, indicating that they were concerned in hypoxia stress and disease responses. Meanwhile, their expression levels were validated utilizing qPCR. Taken together, a greater appreciation and understanding of TLRs function in the reaction to biotic and abiotic stress would ultimately lead to more efficiently environmental adaptation in large yellow croaker.

Unraveling sources of cyanate in the marine environment: insights from cyanate distributions and production during the photochemical degradation of dissolved organic matter - Rui Wang; Jihua Liu; Yongle Xu; Li Liu; Kenneth Mopper (Frontiers in Marine Science, 2024)
Cyanate is a nitrogen and energy source for diverse marine microorganisms, playing important roles in the nitrogen cycle. Despite the extensive research on cyanate utilization, the sources of this nitrogen compound remain largely enigmatic. To unravel the sources of cyanate, distributions and production of cyanate during photochemical degradation of natural dissolved organic matter (DOM) were investigated across various environments, including freshwater, estuarine, coastal areas in Florida, and the continental and slope regions of the North American mid-Atlantic Ocean (NATL). Cyanate production was also examined during the photochemical degradation of exudates from a typical strain of Synechococcus , an important phytoplankton component. To deepen our understanding of the sources and production mechanisms of cyanate, its production was assessed during the photochemical degradation of a natural seawater DOM supplemented with five nitrogen–containing compounds with distinguishing structures and functional groups. Generally, cyanate exhibited higher concentrations in the Florida coastal, estuarine, and freshwater environments than the NATL. However, cyanate distribution did not consistently align with its production rates. Despite significantly low concentrations in the NATL, DOM from this region exhibited cyanate production rates comparable to estuarine and Florida coastal environments. Although relatively high cyanate concentrations were observed in the freshwaters, DOM in this environment exhibited very low cyanate production rates. A highly significant correlation was observed between cyanate and chlorophyll a (Chl a ) concentrations in these areas. Moreover, in most estuarine and NATL stations, cyanate concentration and production rate in the Chl a maximum layer were significantly higher than in other layers. Cyanate was produced during the photochemical degradation of the Synechococcus exudates. The cyanate production was significantly enhanced when the natural seawater DOM was supplemented with GlycylGlycine, 4-(methylamino) benzoic acid, 4-[ethyl(methyl)amino] benzaldehyde or methyl 2-aminobenzoate. Our study implies that photochemical degradation of marine DOM, especially phytoplankton-derived DOM, is a substantial source of cyanate in the ocean. Additionally, cyanate may form during the degradation of peptides and small aromatic compounds in DOM, providing novel insights into the nitrogen cycle.

Recognizing topological attributes and spatiotemporal patterns in spotted seals (Phoca largha) trophic networks based on eDNA metabarcoding - Yan Xu; Fei Huang; Mingliang Zhou; Rui Gu; Jie Zhu; Qiangqiang Rong; Yanpeng Cai (Frontiers in Marine Science, 2023)
Spotted seals, a protected species, face multifaceted threats to their habitat, which in turn impact the closely associated trophic networks. These threats will lead to irreversible structural variations within the ecosystem. Therefore, investigating the topological variability of trophic networks in spotted seals is important. Applying environmental DNA methods, field sample collection was conducted in 2021 during both the sea fishing moratorium period and the fishing period to decode fish diversity. Assessing the current status of fish resources by using the multivariate statistics approach. Applying dietary information establishes the spotted seals’ trophic network. Selecting 12 network indexes to analyze the spatiotemporal patterns of network topological attributes. As a result, about 51 families, and 76 genera species were identified. During the sea fishing moratorium and the fishing period, there are 12 and 18 different food resources available for spotted seals, respectively. The diversity index revealed that the FP had greater species richness and diversity than the SP. Comparatively, the Fishing period exhibited higher species richness and biodiversity, likely influenced by habitat heterogeneity and anthropogenic activities. Additionally, the topological features of networks reflected the high clustering coefficients (CC=0.35) and the proportion of omnivorous species (O≈60%), indicating that the network structure in this region tends to form higher trophic-level clustering patterns, which facilitate the formation of weaker interactions between clusters, enhancing the robustness of the network. The higher connectivity complexity index during the fishing period (SC=12.3) supported that the spotted seal’s trophic network was relatively more stable in this period. Thus, during the fishing period, it is crucial to pay more attention to the intensity of human fishing on mid-to-high trophic-level omnivorous fish resources to ensure the sustainability of these potential food resources for spotted seals. This comprehensive study achieved three key objectives: (a) utilizing eDNA to characterize fish diversity during distinct periods, (b) establishing trophic networks of spotted seals, and (c) discerning topological attributes and spatiotemporal patterns within the ecological network. Overall, this study can provide technical and data support for integrated ecological network management and propose suggestions for protecting and recovering spotted seals.

Editorial: Noise and vibrations in offshore wind farms and their impact on aquatic species - Rui He; Apostolos Tsouvalas; Xiaomei Xu; Lijun Dong (Frontiers in Marine Science, 2023)

Distribution, sources and influencing factors of organic carbon in the surface sediments of the coastal tidal flats in Jiangsu Province - Rui Zhao; Xinrui Dong; Qing Liu; Min Xu; Yifei Zhao (Frontiers in Marine Science, 2023)
Coastal tidal flats are situated in the interaction zone between the ocean and land and are vulnerable to natural changes, human activities, and global changes; these areas serve as an important mixing zone and burial area for carbon and nitrogen storage. Coastal tidal flats contribute significantly to the global carbon cycle due to their high biological productivity, high sedimentation rate, and low decomposition rate. However, there is a lack of research on the sources and influencing factors of organic carbon in surface sediments in the coastal tidal flat area of Jiangsu Province. In this study, fourteen surface sediment samples were collected from the Jiangsu coastal tidal flats, and the distribution of organic carbon was analyzed. The sources and influencing factors of sediment organic carbon were also investigated by analyzing the contents, ratios and stable isotopes of carbon and nitrogen in the sediments. The results indicated that the total organic carbon (TOC) and total nitrogen (TN) contents in the surface sediments of Jiangsu coastal tidal flats ranged from 0.09% to 0.82% and from 0.01% to 0.1%, with mean values of 0.36% and 0.04%, respectively, and that there was a significant positive correlation between TOC and TN. Moreover, the high-value areas were located mostly along the borders or in sections covered in vegetation, whereas the mudflat areas without vegetation had lower values. Considering the status of the Jiangsu coastal zone, the abandoned Yellow River estuary, Yangtze River inlet, marine benthic microalgae, C3 plants and C4 plants were selected as end members of organic carbon concentrations. The contributions of different sources were quantified using a Bayesian mixture model (MixSIAR). Among them, the abandoned Yellow River estuary and Yangtze River inlet contributed 28.1% and 19.3%, respectively, followed by marine benthic microalgae with a contribution of 26%, whereas C3 and C4 plants made limited contributions of 9% and 8.8%, respectively. Additionally, the sediment particle size, hydrodynamics, and tidal flat vegetation such as Spartina alterniflora were the key factors influencing the organic carbon distribution. In general, this study contributes to a better understanding of the biogeochemical processes and sources of organic carbon in coastal tidal flats. It also provides a solid foundation for the creation of carbon sink measures in nearshore tidal flats.

Molecular identification of an insulin-like peptide from the swimming crab Portunus trituberculatus and evidence for its glucoregulation function - Rui Xu; Meng-en Wang; Shisheng Tu; Xi Xie; Dongfa Zhu (Frontiers in Marine Science, 2023)
Insulin-like peptides (ILPs) are essential to the animal kingdom for regulating growth and development, reproduction, behavior, metabolism, and lifespan. In crustaceans, the most well-known ILP is insulin-like androgenic gland hormone, a key hormone in regulating sex differentiation and reproduction. Identification of other ILPs and their functions are still limited. In this study, an insulin-like peptide gene of the swimming crab Portunus trituberculatus was cloned and characterized. Its transcripts were mainly found in nerve tissues and expression could be induced by glucose, implying a putative role in glucoregulation. After depletion of endogenous ILP, injection of ILP dsRNA (dsILP) significantly elevated blood glucose levels and recombinant ILP (rILP) decreased hemolymph glucose levels, further clarifying the involvement of acquired ILP in hemolymph glucose regulation. Injection of dsILP decreased PtAkt , PtGS , PtPFK and increased PtGSK and PtPEPCK gene expression. The opposite profile was observed after glucose and rILP injection, indicating that PtILP might negatively regulate hemolymph glucose levels via the IIS (insulin/IGF-1 signaling) pathway by inhibiting gluconeogenesis and promoting glycogen synthesis and glycolysis. This study has refined the mechanism of glucose regulation in crustaceans and laid the foundation for further studies on ILP function.

Sedimentation of cohesive sediments at the subtidal flat affected by wind wave in high turbidity estuary - Qi Shen; Qin Zhu; Shuguang Liu; Sha Lou; Hualin Wu; Zhenchang Zhu; Bin Xu; Rui Yuan (Frontiers in Marine Science, 2023)
Sedimentation is an important mechanism to mitigate the shrinking of tidal flat and to restore its ecological function by means of sand or mud nourishment. To explore the sedimentation of cohesive sediments, a seabed tripod observation system was deployed at the subtidal region of the Hengsha Shoal adjacent to the turbidity maximum zone of the Yangtze Estuary for 11 days. The results showed that the fine sediment with the median grain size around 8 mm occupied the whole water column. The seabed was in relative equilibrium state with the fluctuation of bed level smaller than 16 mm during the moderate wind condition while the seabed experienced a rapid erosion of 38mm and a successive intensive accretion of 68mm during the process of wind wave and swell. The bottom hydrodynamic at 0.3mab during the bed accretion was stronger than that during the bed erosion. The deposition process of cohesive sediments can be better described by the simultaneous deposition paradigm than that by the exclusive deposition paradigm according to the direct data-model comparison of the bed level changes, especially during the impact of fluid mud. Three possible reasons for the better performance of the simultaneous deposition paradigm were proposed. The first possibility is that the fine suspended sediments do maintain a continuous contact with the sediment bed since the direct bed level changes during our observation period has been well reproduced by the simultaneous deposition paradigm. The second possibility is the SSC-induced turbulence damping which facilitates the fine sediment settling in the form of cohesive sediment flocs, indicating the settling of sediments can’t be judged by the critical shear stress for deposition just based on the single particle grain size. The last possibility is the fluid mud-induced overestimated bed shear stress by using turbulent velocity fluctuation above the fluid mud-water interface, which produces excess sediment erosion waiting to be compensated by the simultaneous deposition paradigm. For practical modeling purposes, modeling under the simultaneous deposition paradigm can give satisfactory results for the sedimentation of cohesive sediment especially during the impact of wave or swell.

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Molecular Characterization and Expression Analysis of Glutaredoxin 5 in Black Tiger Shrimp (Penaeus monodon) and Correlation Analysis Between the SNPs of PmGrx5 and Ammonia-N Stress Tolerance Trait - Rui Fan; Shigui Jiang; Yundong Li; Qibin Yang; Song Jiang; Jianhua Huang; Lishi Yang; Xu Chen; Falin Zhou (Frontiers in Marine Science, 2022)
Glutaredoxins (Grxs) are glutathione-dependent oxidoreductases that belong to the thioredoxin (Trx) superfamily and are an essential part of the redox system in living organisms. However, there is a serious lack of sequence information and functional validation associated with Grxs in crustaceans. In this study, a new Grx gene ( PmGrx5 ) was identified and characterized in black tiger shrimp ( Penaeus monodon ). The full-length cDNA of PmGrx5 is 787 bp and consists of 114 bp 5′-UTR, 232 bp 3′-UTR, and 441 bp ORF, encoding a hypothetical protein of 146 amino acids. The putative PmGrx5 protein is 16.27 kDa with a theoretical isoelectric point of 5.90. Sequence alignment showed that PmGrx5 had the highest amino acid sequence homology with Grx5 from Penaeus vannamei at 98.63% and clustered with Grx5 from other crustaceans. Quantitative real-time PCR (qRT-PCR) analysis showed that PmGrx5 was expressed in all tissues examined, with a higher expression in the testis, stomach, lymphoid organ, and gill. PmGrx5 was continuously expressed during development, with the highest expression in zoea I. Ammonia-N stress and bacterial infection both differentially upregulated PmGrx5 expression in the hepatopancreas and gill. In addition, when PmGrx5 was inhibited, the expression of some other antioxidant enzymes was upregulated at the beginning of ammonia-N stress, but as the stress time increased, the expression of antioxidant enzymes was inhibited, the expression of apoptotic genes was increased, and the GSH content was significantly reduced. Inhibition of PmGrx5 led to a greater risk of oxidative damage in shrimp. In addition, the relationship between SNPs in exons of the PmGrx5 gene and tolerance to ammonia-N stress was identified and analysed. A total of nine SNPs were successfully identified, eight of which were significantly associated with ammonia and nitrogen stress tolerance trait in shrimp ( P < 0.05). The present study shows that PmGrx5 is involved in redox regulation and plays an important role in shrimp resistance to marine environmental stresses. Meanwhile, this study will provide a basis for molecular marker breeding in shrimp.

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)